Rumors and rumor control : a manager's guide to understanding and combatting rumors - Kimmel, Allan J. (LEA's communication series., 2004)
This project offers a thorough examination of rumours and proposes strategies for organizations to use in combatting rumours that occur both internally and externally. Author Allan J. Kimmel explores the rumour phenomenon and distinguishes it as a distinct form of communication.